Contending with Stanley Cavell - Cavell, Stanley, 1926-2018; Goodman, Russell B. (Oxford University Press, 2005)
This collection showcases Stanley Cavell's work, while illustrating the variety of Cavell's interests: in the ordinary language philosophy of Wittgenstein and Austin, in film criticism and theory, in literature, psychoanalysis, and the American transcendentalism of Ralph Waldo Emerson and Henry David Thoreau.